Belogurov V.V. - Azarnova Т.О.; Вorkhunova E.N.; Kachalin M.D.; Pozyabin S.V. (Ветеринария и кормление)
It is known that latent pathologies, especially in the area of the hoof bone, lead to a violation of horn formation, which, in turn, leads to a decrease in the protective function of the horny shoe. All these factors are prerequisites for extensive lesions of the distal extremities in cattle under production conditions. Based on the results of a clinical examination and X-ray examination in two farms of the Moscow region in dairy cattle, the prevalence of latent pathologies of the distal extremities was revealed. Most often, we identified such pathologies of the distal extremities as aseptic periostitis, 100% of the examined animals had pronounced changes in the form of periosteal periosteal reactions. The hoof and crown bones were most affected. We found that periostitis most often developed at the sites of attachment of ligaments and tendons. The second most common pathology of the fingers of cattle during radiography is arthrosis of the hoof and crown joints, which occurred in 55 and 79.5% of cases in the examined animals. It was also found that the number of purulent-necrotic lesions, including bone structures of the distal extremities in dairy cattle, is higher during X-ray examination, because, with such pathologies, it is impossible to correctly assess the depth of the lesion during orthopedic medical examination without X-ray examination. It was found that the irregular shape of the hooves, horn stratification, horn formation disorder, which were a sign of a complex lesion of several structures of the finger, laminitis, a specific ulcer of the sole, which required deeper surgical treatment. Thus, it can be concluded that a clinical examination of an animal and orthopedic medical examination without the use of special studies may not give a complete picture of the nature of pathological changes in the hooves of cattle. This, in turn, leads to an incorrect assessment of the number of animals with orthopedic pathologies in dairy farms.